Spatial and temporal variation Trend Analysis of vegetation cover in Urban agglomeration of Pearl River Delta from 2000 to 2015. Issue 1 (December 2020) - Zhang, Dong; Wu, Fengzhi; Fang, Yanzhuo; Lu, Ni
Abstract: Based on MODIS NDVI remote sensing data, the methods of regression analysis, CV stability analysis, Hurst exponent analysis are used to invert the spatio-temporal variation trend of vegetation cover in the Pearl River Delta region from 2000 to 2015. On this basis, the future change trend of vegetation cover was predicted. The results indicate that (1) the vegetation coverage in the Pearl River Delta was on a rising trend in general from 2000 to 2015 (0.029/10 years). (2). The vegetation change in The Pearl River Delta region was mainly significantly improved (39.73%), and significantly degraded and slightly degraded areas accounted for only 13.22%, which were staggered with significantly improved regions. (3) Degree of vegetation cover fluctuation in cities and surrounding areas has significant spatial consistency with degraded areas of vegetation cover, which indicates that there is a certain correlation between the change of vegetation cover around the city and human activities. (4) Combined with the analysis of future and past trends, the condition that vegetation cover firstly degrades and then improves will occur. While vegetation degradation may occur in non-urban concentrated areas without good ecological planning. The research results will be helpful to understand the trend and spatial distribution of vegetation in the Pearl River Delta region.